Analisis Rasio Keuangan Untuk Mengukur Kinerja Keuangan Pada Pt. Sumber Alfaria Trijaya Tbk - Nurhikmah Maharani; Zainal Ruma; Andi Mustika Amin; Anwar Ramli; Hety Budiyanti (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This study aims to determine and analyze financial performance using financial ratio analysis in PT. Sumber Alfaria Trijaya Tbk. Period 2018-2022. This type of research is descriptive quantitative research. The research was conducted through the official website of the Indonesia Stock Exchange (IDX). The population in this study is all financial statements of retail companies in the supermarket and minimarket subsector listed on the Indonesia Stock Exchange for 2018 - 2022, while the sample of this study is PT. Sumber Alfaria Trijaya Tbk for the period 2018-2022. The data collection technique in this study is documentation while the data analysis technique uses financial ratios namely liquidity ratio, solvency ratio, activity ratio and profitability ratio and market value ratio. The results showed that the level of financial ratios of PT. Sumber Alfaria Trijaya Tbk. tends to be above the industry standard average which shows financial performance is in good condition.